Reciprocating sliding wear of case-hardened spheroidal cast iron against 100Cr6 under boundary lubrication. (October 2015) - Stickel, D; Goeke, S; Geenen, K; Huth, S; Theisen, W; Biermann, D; Fischer, A
Today cast iron with spheroidal graphite is used in a wide range of applications with a high production capacity per year. Due to optimized and well-controlled casting technology, the production of ductile cast iron became economic in such way that ductile cast iron replaced cast or wrought steel in many machinery components like crankshafts, piston rods, and engine mounts. These examples represent technical tribosystems of the automobile industry. Here, current political, economic, and ecological guidelines also demand downsizing combined with high power densities in order to minimize internal friction and reduce fuel consumption and satisfying CO2 -emission limits. These guidelines can change the tribological loads and, therefore, result in more severe conditions. One example is the shift of the lubrication regime from hydrodynamic to mixed or boundary lubrication for larger periods of time. In these regimes, the applied load is partially or fully carried by the asperities. Still the need for maintaining as low as possible wear towards the ultra-mild sliding wear regime an integral approach is needed, which has to regard contact conditions, surface topography, interface chemistry, and sub-surface properties. One way to low wear can aim at lowering the run-in phase by e.g. optimizing the topography by means of adjusted machining processes. For this study, reciprocating sliding wear tests were conducted with grinded, milled, polished, and finished samples of case-hardened spheroidal cast iron slid against a 100Cr6 ball of a 5 mm radius. The boundary lubrication was provided by a commercial combustion engine lubricant at 80℃. After predefined test cycles, 3D surface topographies were measured by means of confocal white-light microscopy within each wear test in order to analyse the development of the contact conditions over time. In combination with the measured forces and displacements, the tribological loads are calculated by means of a 3D elastic-ideal plastic contact model. Additionally the wear mechanism was analyzed by means of scanning electron microscopy. The overall wear rates and the coefficients of friction depend strongly on the initial surface topography and, therefore, on the machining process. This is also true for the development of a reaction layer (tribomaterial) allowing for ultra-mild siding wear even under boundary lubrication.